A further enhancement of n-gram algorithm for accurate and precise word prediction - Cheska Deniece S. Baldueza and Cristine Aira C. Benitez. 4 0 16; 5 (2014)
u
Undergraduate Thesis: (Bachelor of Science in Computer Studies major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2